The electronic spectrum of selenium dioxide - Crowther, S (2003)
The C͂¹B₂ ←　X͂¹A₁ electronic transition of SeO₂ has been investigated under high resolution, at a rotational temperature of around 10 K, using the technique of Laser Excitation Spectroscopy. The vibrationally-resolved survey spectrum contained around 100 new bands in addition to the bands which had been reported in a previous study of the same region (G.W. King and P.R. McLean, J. Mol. Spec. 51, 1974). In the light of this new spectrum a number of bands have been reassigned, most significantly the O⁰₀ band, and a number of progressions have been extended. This led to a revised determination of the vibrational constants of the excited state, and a more acceptable estimate of v'₃ than was suggested in the previous work. These reassignments and extensions of existing assignments accounted for only a small fraction of the newly observed bands; those remaining are thought to be due to a different electronic transition which lies in the same region as the C͂¹B₂ ←　X͂¹A₁ transition. The 1³₀, 1²₀ and 1¹₀ bands of the C͂¹B₂ ←　X͂¹A₁ transition were also recorded at rotational resolution and analysed using the method of ground state combination differences. The 1³₀ band was found to be perturbed, which was one of the major factors which prompted the survey study described above. From the analysis of these bands the rotational constants of the excited state were determined and hence the geometry of the SeO₂ molecule in the given vibrational levels of the ¹B₂ excited state was calculated. This in turn enabled the rotational constants and the geometry of the (00) vibrational level of the excited state to be estimated. This work confirms that the symmetry of the excited state is ¹B₂ and the transition studied is C͂¹B₂ ←　X͂¹A₁. An additional band around 31957 cm⁻¹ was also recorded at rotational resolution, which was initially though to be the O⁰₀ band, on the basis of King and McLean's assignments. However in the light of the reassignments the nature of this band is not known, and attempts to assign it as vibrationally cold band of the C͂¹B₂ ←　X͂¹A₁ transition were unsuccessful, implying that it is probably either a hot band of the C͂¹B₂ ←　X͂¹A₁ transition or a band belonging to different electronic transition.